Overcoming the limited availability of human milk oligosaccharides: challenges and opportunities for research and application - Bode, Lars (Nutr Rev, 2016)
Human milk oligosaccharides (HMOs) are complex sugars highly abundant in human milk but currently not present in infant formula. Rapidly accumulating evidence from in vitro and in vivo studies, combined with epidemiological associations and correlations, suggests that HMOs benefit infants through multiple mechanisms and in a variety of clinical contexts. Until recently, however, research on HMOs has been limited by an insufficient availability of HMOs. Most HMOs are found uniquely in human milk, and thus far it has been prohibitively tedious and expensive to isolate and synthesize them. This article reviews new strategies to overcome this lack of availability by generating HMOs through chemoenzymatic synthesis, microbial metabolic engineering, and isolation from human donor milk or dairy streams. Each approach has its advantages and comes with its own challenges, but combining the different methods and acknowledging their limitations creates new opportunities for research and application with the goal of improving maternal and infant health.